COVID-19 impact on artistic income - Cuntz, Alexander; Sahli, Matthias (World Intellectual Property Organization, 2021)
This paper assesses the impact of the pandemic crisis on self-employed income among artists resident in Germany. Using unique data from the latest available public insurance records, we show that musicians and performing artists are among the most vulnerable groups, and that writers, on average, are relatively less impacted. Moreover, the paper looks at the impact of the 2020 crisis on income differences by gender, career stages and regions, and it investigates the effect of specific non-pharmaceutical, public intervention implemented in German states.
"September 1, 2021."
"JEL codes: J00, J08, E24, Z11."
Keywords: COVID-19 Pandemic, 2020-; COVID-19 (Disease) -- Economic aspects.; Art -- Economic aspects.; Artists -- Germany.